2015
DOI: 10.1007/s11926-014-0485-9
|View full text |Cite
|
Sign up to set email alerts
|

The Journey of Antiphospholipid Antibodies From Cellular Activation to Antiphospholipid Syndrome

Abstract: Pathogenic antiphospholipid antibodies (aPL) are the driving factors of recurrent pregnancy loss and thrombosis that characterize antiphospholipid syndrome (APS). Current evidence indicates that aPL induce a procoagulant phenotype in the vasculature and abnormal cellular proliferation and differentiation in placental tissues to cause the typical clinical features; however, the molecular mechanisms underlying these processes remain incompletely understood. Inflammation serves as a necessary link between the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 100 publications
(103 reference statements)
1
19
0
2
Order By: Relevance
“…APS can occur on its own or in association with other autoimmune diseases, most commonly systemic lupus erythematosus (SLE) [2]. A combination of genetic and environmental factors is thought to be responsible for the formation of these antibodies [3]. The diagnosis of APS requires (1) one or more specific clinical events such as a vascular thrombosis and/or an adverse obstetric event and (2) the confirmed presence of a repeatedly positive aPL [4].…”
Section: Introductionmentioning
confidence: 99%
“…APS can occur on its own or in association with other autoimmune diseases, most commonly systemic lupus erythematosus (SLE) [2]. A combination of genetic and environmental factors is thought to be responsible for the formation of these antibodies [3]. The diagnosis of APS requires (1) one or more specific clinical events such as a vascular thrombosis and/or an adverse obstetric event and (2) the confirmed presence of a repeatedly positive aPL [4].…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies have been hypothesized to have the potential to exacerbate inflammation-mediated tissue injury. 15 However, Ardiles et al found no difference of degree of renal injury, glomerular abnormalities in urine and creatinine levels in clinical follow-up between aCL-positive patients and aCL-negative patients with APSGN. 2 It is considered that aCL can be associated with a thrombotic risk if persistently elevated.…”
Section: Discussionmentioning
confidence: 96%
“…Se ha propuesto la hipótesis de que estos anticuerpos podrían potencialmente exacerbar la lesión tisular mediada por la inflamación. 15 Sin embargo, Ardiles y col. no hallaron diferencias en el grado de lesión renal, en las anomalías glomerulares en la orina ni en la concentración de creatinina durante el seguimiento clínico de los pacientes con GNAPE que tenían resultados positivos para los anticuerpos contra la cardiolipina y aquellos con resultados negativos. 2 Se considera que los anticuerpos contra la cardiolipina pueden estar asociados con un riesgo de trombosis si permanecen elevados.…”
Section: Discussionunclassified